Numérique à l'École - usages, ressources, métiers, industries - Gérard Puimatto (Centre National d'Enseignement à Distance, 2014)
For about fifteen years digital uses in school have been the object of proactive policies, but contradictory trends - rapid development and substantial limitations - are still at play. Since 2007, Corrélyce (a regional system of management for accessing online resources) has adopted an original strategy, founding the development of digital uses in school, on editorial online resources. Corrélyce is subjected to annual surveys about the uses of the resources, and some major orientations can thus be highlighted: if access to resources can be a lever of evolution for the teaching profession, this possibility is restricted by an unclear relation to resources and by the strong institutional character of their prescription. At this stage, existing devices create conditions for accessing resources, but do not really enable the full integration of pedagogical uses in classrooms practices. This project is taking shape today, providing a framework for the production and dissemination of resources, for the development of professional teaching skills and for educational industries.